Enabling disaster resilience in Parang, Marikina by fostering social cohesion in the integrated design of public spaces and evacuation centers - Cruz, Lerion Allister R. (College of Architecture, University of the Philippines Diliman, 2022)
In an urban environment, it is common that social interactions become anonymous exchanges between strangers. In the context of Metro Manila, this creates segregated communities exacerbated by the prevailing environment of exclusivity in our public spaces. Our malls and shopping centers lock out low-income demographics and parks, courts, and even homes are walled within exclusive villages. This hinders the development of the social infrastructure and the fostering of social trust that is necessary in the building of resilient communities in the event of a disaster. This presents a problem as cities will be facing much more risks in the future, especially to weather hazards due to climate change. The site for this project is located in Barangay Parang, Marikina City. It is an increasingly urbanizing city that is vulnerable to heavy flooding due to its geographic location as a valley plain with a river bisecting the city through its center. It is expected that due to climate change, the vulnerability of this city to floods will only increase due to the rising severity of weather events. This thesis explores for potential design solutions in improving the disaster resilience of the communities vulnerable to these increasing climate hazards. It does this through the approach of combining public spaces with disaster response and management functions. The relationships between space and social formation were studied to create a disaster resilient community through social cohesion. Combined with a thorough analysis of the site and its users, it aims to deliver an architectural design proposal that encourages social, cultural, and economic exchange within the functions of a structure that is both a public recreational space and an evacuation center.